Frequency of Radial Nerve Palsy in Patients with Closed Traumatic Humeral Shaft Fracture in High Energy Trauma Cases - Muhammad Ali, Muhammad Moazzam Khan, Umair Ahmad, Ashfaq Jadoon, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Different pattern of the fractures of the humerus shaft usually result in radial nerve injury. The frequent injury of radial nerve is because of its close proximity to the humeral shaft in the radial groove. Objective: Determining the incidence of Radial Nerve Injuries in Patients with Closed type of Humeral Shaft Fractures in high-energy trauma cases. Material and Methods:Department of Orthopedics conducted this study at Ghurki Trust & Teaching Hospital, Lahore from January 2021 to December 2021, including all patients regardless of gender, aged between 20-60 years with closed fractures at the level of shaft of humerus. All the patients were thoroughly investigated with detailed history, clinical and radiological examination. The patients were originally managed according to standard ward procedures, fracture stabilization with U-slab and analgesic requirements. All of the patients were clinically examined to rule out radial nerve damage. The data accumulated after completion was analyzed using the relative software SPSS version 26.0. Results: This study included 80 patients with radiologically confirmed humeral shaft fractures. There were 55 (68.5%) men and 25 (31.25%) women having this type of fracture pattern. The participants ages were inbetween 20 to 60 years, with men and women having mean ages of 31.62 ±8.35 years and 38.43±5.06 years, respectively, and overall mean age of 38.93± 6.19 years. Spiral fractures accounted for 32 (40%) of the cases, while transverse fractures17 (21.25%), communited fractures16 (20%) and segmental fractures 15(18.75%). In 7 (or 8.75 percent) out of the 80 patients, radial nerve injury was observed. 4 (57.1%) cases of radial nerve damage were found in patients with spiral closed midshaft humerus fractures, 1 (14.3%) reported case in transverse closed humerus shaft fractures, 1 (14.3%) case in comminuted closed midshaft humerus fractures, and 1 (14.3%) case in segmental fractures. Conclusion: This study highlighted the frequency of radial nerve palsy among the patients with humeral shaft fractures at spiral goove . Radial nerve palsy was found in 8.75% of cases presented to our setup.Most of these cases reported in patients with spiral type of fracture of humerus midshaft. These findings are helpful to the surgeons during the pre operative counseling of patients, who suffered radial nerve damage due to a humerus shaft fracture at radial groove. Keywords:Radial Nerve Injury, Closed fracture of the humerus, Radial groove ,Humerus Shaft